The Effect of Leadership, Compensation, and Work Environment on Employee Work Spirit : Study at CV. Subur Makmur, Japan Village, Babadan District, Ponorogo - Sri Aning; Sri Hartono; Wijianto (Malaqbi Publisher, 2026)
This study aims to analyze the influence of Leadership, Compensation and Work Environment on Employee Work Spirit at CV. Subur Makmur Japan Village, Babadan District, Ponorogo. Based on the results of the discussion in accordance with the data managed with a multiple linear regression analysis model, it is concluded that; Based on the results of the t test of the independent variable of the influence of Leadership , the calculated t value <t table (1.956<2.042), then Ho is accepted, meaning there is no influence of Leadership on Employee Work Spirit. Compensation, the calculated t value > t table (2.091>2.042) then Ho is rejected, meaning there is an influence of Compensation on Employee Work Spirit. Work Environment, obtained the calculated t value > t table (2.072 > 2.042) then Ho is accepted, meaning there is no influence of the Work Environment on Employee Work Spirit. Meanwhile, based on the results of the F test of the dependent variable Employee Work Spirit, obtained the calculated F value > F table (6.229 > 2.87) then Ho is rejected, meaning there is an influence of Leadership, Compensation and Work Environment together/simultaneously on Employee Work Spirit.